Association of Vitamin D Receptor Polymorphisms With Activity of Acromegaly, Vitamin D Status and Risk of Osteoporotic Fractures in Acromegaly Patients - Jawiarczyk-Przybyłowska, Aleksandra; Halupczok-Żyła, Jowita; Kolačkov, Katarzyna; Gojny, Łukasz; Zembska, Agnieszka; Bolanowski, Marek (Frontiers in Endocrinology, 2019)
Introduction: The vitamin D receptor (VDR) gene is one of the most widely studied tumorigenesis-related genes. The primary objective of this study was assessment of possible roles of VDR gene polymorphisms in acromegaly with regard to the activity of the disease and compared them with a control group. Furthermore, we have assessed the associations between these polymorphisms with vitamin D status as well as with TBS (trabecular bone score) and risk for osteoporotic fracture in acromegaly patients. Materials and methods: We studied 69 patients with acromegaly and 51 healthy controls (CG). Acromegaly patients were divided into three subgroups on the basis of disease activity (AA - active acromegaly, CD - controlled disease and CA - cured acromegaly). In all patients blood samples were obtained to assess the hormonal and metabolic status as well as genetic analysis. VDR polymorphisms were determined by means of two methods, Polymerase Chain Reactions (PCR) and minisequencing (SNaPshot). Results: Genotype frequencies for VDR ApaI, TaqI, BsmI and FokI polymorphisms did not deviate significantly from Hardy-Weinberg equilibrium (HWE) in the acromegaly group as well as in the control group. There was no statistically significant difference in distributions of these four VDR genotypes between acromegaly patients and the control group. This study revealed statistically significant negative correlation between risk of major osteoporotic fractures and genotypes tt (TaqI), aa (ApaI) and bb (BsmI) in acromegaly groups. Furthermore, the negative correlations were observed between TBS and risk for major osteoporotic fractures and hip fractures. Conclusions: Our study suggests that tt (TaqI), aa (ApaI) and bb (BsmI) of VDR gene may be associated with better bone quality and microarchitecture (higher TBS), which lead to a lower risk of osteoporotic fractures in acromegaly patients. TBS may be a useful tool for predicting risk of fractures in acromegaly patients.